Iowa Birdline update, January 25, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for January 25, 1993. Highlights of the update include sightings of the continued presence of the two Townsend's Solitaires, a Long-tailed Duck and two Trumpeter Swans. Also included are handwritten notes for the next week's update with sightings of a Northern Saw-whet Owl, a first year Glaucous Gull and two Wood Ducks. Epson - sheet feed/flatbed